The impact of office machinery and computer capital on the demand for heterogeneous labor - Martin Falk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper analyzes the impact of office machinery and computer capital (OCM) on the demand for heterogeneous labor. A system of static and dynamic factor demand equations based on a variant of the generalized Box-Cox cost function nesting the translog, the generalized Leontief and the normalized quadratic functional form is derived and estimated. OCM capital and general capital are treated as quasi-fixed factors. Using panel data on 35 German industries, we find that OCM capital is complementary to all skill levels. For the manufacturing sector, the increase in OCM capital and general capital has accounted for at least 60 percent and 9 percent of the expanding employment of university graduates. In nonmanufacturing industries, we find that an increase in general capital tends to reduce unskilled workers. Wage effects and substitution effects between different types of labor and material inputs play a minor role in explaining employment changes of highly skilled workers and medium-skilled workers but these effects are more important in explaining the demand for unskilled workers.
Keywords: J23; O33; 330; skill-biased technological change; capital-skill complementarity; Büromaschine; Informationstechnik; Computergestütztes Verfahren; Arbeitsnachfrage; Qualifikation; Kostenfunktion; Schätzung; Deutschland